COVID-19 in congenital heart disease (COaCHeD) study - Ashish Chikermane; Konstantinos Dimopoulos; Michael A Gatzoulis; Sonya V Babu-Narayan; Zdenka Reinhardt; Natali AY Chung; Paul F Clift; Dirk Wilson; Petra Jenkins; Rachel Knowles; Bernadette Khodaghalian; Benjamin Smith; et al. (Open Heart, 2023)
Background COVID-19 has caused significant worldwide morbidity and mortality. Congenital heart disease (CHD) is likely to increase vulnerability and understanding the predictors of adverse outcomes is key to optimising care.Objective Ascertain the impact of COVID-19 on people with CHD and define risk factors for adverse outcomes.Methods Multicentre UK study undertaken 1 March 2020–30 June 2021 during the COVID-19 pandemic. Data were collected on CHD diagnoses, clinical presentation and outcomes. Multivariable logistic regression with multiple imputation was performed to explore predictors of death and hospitalisation.Results There were 405 reported cases (127 paediatric/278 adult). In children (age <16 years), there were 5 (3.9%) deaths. Adjusted ORs (AORs) for hospitalisation in children were significantly lower with each ascending year of age (OR 0.85, 95% CI 0.75 to 0.96 (p<0.01)). In adults, there were 24 (8.6%) deaths (19 with comorbidities) and 74 (26.6%) hospital admissions. AORs for death in adults were significantly increased with each year of age (OR 1.05, 95% CI 1.01 to 1.10 (p<0.01)) and with pulmonary arterial hypertension (PAH; OR 5.99, 95% CI 1.34 to 26.91 (p=0.02)). AORs for hospitalisation in adults were significantly higher with each additional year of age (OR 1.03, 95% CI 1.00 to 1.05 (p=0.04)), additional comorbidities (OR 3.23, 95% CI 1.31 to 7.97 (p=0.01)) and genetic disease (OR 2.87, 95% CI 1.04 to 7.94 (p=0.04)).Conclusions Children were at low risk of death and hospitalisation secondary to COVID-19 even with severe CHD, but hospital admission rates were higher in younger children, independent of comorbidity. In adults, higher likelihood of death was associated with increasing age and PAH, and of hospitalisation with age, comorbidities and genetic disease. An individualised approach, based on age and comorbidities, should be taken to COVID-19 management in patients with CHD.